A rare incidental finding of splenogonadal fusion in a trauma patient: A case report and review of the literature - Mosleh, Shammout (2025)
The unusual fusion of splenic tissue with gonadal or mesonephric tissue remains is the hallmark of a rare congenital condition known as splenogonadal fusion (SGF). It arises during embryological development due to the proximity between the splenic anlage and gonadal mesoderm, typically between the 5th and 8th weeks of gestation. Even though SGF is typically asymptomatic, it is most commonly discovered by accident during imaging, surgery, or autopsy. Here, we present the case of a 17-year-old male who sustained pelvic fractures after a fall from height. Hemoperitoneum, right sacral ala and left iliac fractures, bilateral pubic rami fractures, and an incidental finding of continuous SGF were also discovered during imaging. Multidisciplinary review and imaging confirmed the congenital abnormality.Conservative treatment of pelvic fractures and follow-up assessment of SGF, including genetic counseling, were the main goals of management.